Improving Students' Basic Asking Skills by Using the Discovery Learning Model - Kusuma, Raden Septa (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2020)
The aim of this research is to determine the effectiveness of the model Discovery Learning to improve basic questioning skills. The method used in this research is action research class, intended to obtain information regarding the effectiveness of the Discovery Learning model for improving basic questioning skills. The subjects in this research were class III B students at elementary school 64/1 Muara Bulian. Data analysis was carried out to test the research hypothesis. Analysis The research uses qualitative analysis and quantitative analysis. The results obtained indicate that the Discovery model is used Learning in improving students' basic questioning skills goes by good with improvements in each cycle and can reach the criteria research success. This research offers novelty by focusing on the use of the Discovery Learning Model to improve students' basic questioning skills in class III B at elementary school 64/I Muara Bulian. The Discovery Learning model is a learning approach that emphasizes exploration, discovery and developing students' questioning skills through an active and in-depth learning process. By applying this model, this research presents a different and innovative learning approach in developing students' questioning skills, which is expected to make a significant contribution to improving the quality of learning at the elementary school level.